KWARTET: PRESERVING THE CULTURE BY PLAYING IT - Ilmi, Bachrul; Salim, Tamara Adriani (PEOPLE: International Journal of Social Sciences, 2018)
Tradition, art and culture are part of the nation's identity. Where each person as a member of nation has an obligation to preserve it. This paper aims to explain how traditions, art and culture are preserved through the game named "Kwartet Eskabe" in Banyuwangi, East Java. This game gives the children knowledge by games concerning one's their own culture in a fun way, but they still get the essence of cultural preservation inside. This research uses qualitative approach and the result is presented descriptively. Data obtained from interviews, observation, documentation. This study involved several parties, namely the founder of Kampoeng BATARA as an informant who was also part of the independent organization "Sengker Kuwung Blambangan", children-members of Kampoeng BATARA as participant of practice, first author as purpose determining of research, and second author as adviser. The result shows that Kwartet games: (1) can be a medium to transfer culture value through culture embedded in the card and game rules; (2) transfer knowledge of culture occurred in Kwartet Eskabe game are internalization and externalization; and (3) the preservation of knowledge occurred is selection, storage, actualization, where cultural knowledge is selected, poured in the card form and understood by the players. The study is limited to Kwartet Eskabe games, that placed in Banyuwangi district, Indonesia. Thus, the discussion of games in the other regions will be restricted. This paper will be helpful for the society to teach the culture, tradition, can be conducted by pleasure way. Such way can also preserve the culture and tradition with playing it by children who are as the next generation, so that the culture can be embedded in their mind, furthermore the children will spread this game to their other friends. In the end, the essence of the culture embedded in the Kwartet Eskabe can be widely recognized by others.